Transformation of Internet of Things-Based Volleyball Training: Analysis of its Development and Prospects in Modern Sport Science - Jianie Lutfiatul Putri; Gea Charina Cahaya Putri; Annisa Wahyu Ramadhani; Limpad Nurrachmad (Jurnal Multidisiplin Sahombu, 2026)
The Internet of Things (IoT) is increasingly integrated into sports to provide accurate, real-time performance data. In volleyball, IoT technologies support technique analysis, athlete monitoring, and training load management through sensors, microcontrollers, and wearable devices. This study presents a narrative review of literature published between 2020 and 2025 to map the development o IoT in volleyball training. Findings indicate that IoT enhances technical evaluation and training control, yet its implementation in Indonesia remains limited. Further development of affordable devices and multi-sensor integration is needed to expand IoT adoption in future volleyball training practices.